Status of CRYRING@ESR and preparations for first experiments. Issue 23 (January 2020) - Lestinsky, M; Andelkovic, Z; Bai, M; Bräuning-Demian, A; Chetvertkova, V; Fedotova, S; Geithner, O; Geithner, W; Gorda, O; Herfurth, F; Kalinin, A; Källberg, A; et al.
Synopsis: CRYRING was moved from Stockholm to Darmstadt, modernized and integrated into the GSI/FAIR beamline topology behind ESR. As CRYRING@ESR, it will receive and store heavy, highly charged ions from all species the present accelerator chain is capable of producing. An extensive research program on low-energy atomic collisions, spectroscopy and nuclear reactions was proposed. The facility is gradually completing commissioning, ion beams from the local injector branch have already been stored and prototype experiments performed. We present the machine status and highlight some planned experiments.